he Experimentoteca of Universidade Federal do Espírito Santo: An approach of Scientific Education - Palmeira Bellon, Patricia; Bortolin Lourenço, Gabriel Luis; Teixeira Bragança, Sanmila; Bitencourt Ramos, Italo; Evangelista dos Santos, Lucas; Borges Corte, Viviana (Guará Journal, 2019)
In  2018  the  Public  Experimentoteca  Project:  Scientific Education Through Experimental  Practices celebrates 20  years  as  one  of  the  most long-standing projects of the Universidade Federal do Espírito Santo. Among his activities are the initial and continuing education of teachers  in  the  area  of  Natural  Sciences, as well  as the promotion of instruments to improve the quality of  science  classes  in  primary and secondary education. We aim to present a brief history of the Project, as well as the services provided to basic education and teacher training since 2010, as well as its current perspectives and future potential of acting in the teaching of Sciences in Espírito Santo. As a result, we have the diffusion, through loans of teaching kits for schools,  as  well  as  the  dissemination  of  science  and improvement  of education through courses for teachers and students of primary, secondary education and undergraduate degree, as well as exhibitions  at scientific  fairs.  In  the  first  half  of  2018,  more  than 3700  stu-dents  of  basic  education  were  attended between  workshops  held  inside and outside the University. During the experimental activities the students showed great interest and involvement. It is concluded, therefore,  that  scientific diffusion  through experimental  practices is of the utmost importance for the improvement of science education.
Keywords: Scientific education; Popularization of science; Continuing education; Scientific literacy